Risk and Profitability of Islamic Banking in Indonesia : Granger Causality Test - Rakhmat, Adrianna Syariefur; Nurastuti, Preatmi; Fahamsyah, Mohammad Hatta (DPPM Universitas Pelita Bangsa, 2023)
This research discusses the two-way relationship between financing risk and profitability in Islamic banks. This research is a quantitative study. The data used is secondary data sourced from the Financial Services Authority regarding Islamic Bank Financing Risk or Non-Performing Financing (NPF) and Islamic Bank Profitability or Return on Assets (ROA) in June 2014-June 2023. This research tests the two-way relationship between NPF and ROA using the Granger Causality Test. This research finds that there is only a one-way relationship between ROA and NPF.